An Ethylenediamine‐based Switch to Render the Polyzwitterion Cationic at Tumorous pH for Effective Tumor Accumulation of Coated Nanomaterials. (23rd March 2018) - Ranneh, Abdul‐Hackam; Takemoto, Hiroyasu; Sakuma, Shunya; Awaad, Aziz; Nomoto, Takahiro; Mochida, Yuki; Matsui, Makoto; Tomoda, Keishiro; Naito, Mitsuru; Nishiyama, Nobuhiro
Abstract: Polyzwitterions are employed as coating polymers for biomaterials to induce an antifouling property on the surface. Fine‐tuning the betaine structure switches the antifouling property to be interactive with anionic tissue constituents in response to a tumorous pH gradient. The ethylenediamine moiety in the carboxybetaine enabled stepwise protonation and initiated the di‐protonation process around tumorous pH (6.5). The net charge of the developed polyzwitterion (PGlu(DET‐Car)) was thus neutral at pH 7.4 for antifouling, but was cationic at pH 6.5 for interaction with anionic constituents. Quantum dots coated with PGlu(DET‐Car) exhibited comparable stealth and enhanced tumor accumulation relative to the PEG system. The present study provides a novel design of smart switchable polyzwitterion based on a precise control of the net charge.